Atypical fulminant Rickettsia rickettsii infection (Brazilian spotted fever) presenting as septic shock and Adult Respiratory Distress Syndrome - Paulo Sérgio Gonçalves da Costa; Marcos Emilio Brigatte; Edmilton Pereira de Almeida; Lena Márcia de Carvalho Valle (Brazilian Journal of Infectious Diseases)
Brazilian spotted fever, caused by Rickettsia rickettsii, has been increasingly reported in Brazil especially in the southeastern states. The severe and fulminant forms of the disease are not unusual but most of the reported fatal cases have shown some typical clinical clue, which leads the attending physician to a correct diagnosis. We report a probable case of atypical fulminant Brazilian spotted fever that presented full-blown septic shock associated with Adult Respiratory Distress Syndrome (ARDS) and delayed uncharacteristic rash with an over four-fold increase in reciprocal IgM, but not IgG titer against Rickettsia rickettsii. Brazilian practitioners should be aware of the possibility of Brazilian spotted fever as a cause of fulminant primary sepsis with ARDS; improved laboratory methods are necessary for the rapid diagnosis of such cases.